Class 3 phosphoinositide 3‐kinase promotes hepatic glucocorticoid receptor stability and transcriptional activity. (7th February 2022) - Shibayama, Yui; Alkhoury, Chantal; Nemazanyy, Ivan; F Henneman, Nathaniel; Cagnard, Nicolas; Girard, Muriel; Atsumi, Tatsuya; Panasyuk, Ganna
Abstract: Aim: Lipid kinase class 3 phosphoinositide 3‐kinase (PI3K) and nuclear receptor transcription factor glucocorticoid receptor (GR) play essential physiological roles in metabolic adaptation to fasting by activating lysosomal degradation by autophagy and metabolic gene expression, yet their functional interaction is unknown. The requirement of class 3 PI3K for GR function was investigated in liver tissue. Methods: Inactivation of class 3 PI3K was achieved through deletion of its essential regulatory subunit Vps15, by expressing Cre‐recombinase in the livers of Vps15 f/f mice. The response to both 24‐h fasting and synthetic GR ligand, dexamethasone (DEX) was evaluated in control and mutant mice. Liver tissue was analysed by immunoblot, RT‐qPCR, and LC‐MS. Results: Vps15 mutant mice show decreased transcript levels of GR targets, coupled with lower nuclear levels of total and phosphorylated on Ser211, GR protein. Acute DEX treatment and 24‐h fasting both failed to re‐activate expression of GR targets in the livers of Vps15 mutant mice to the levels observed in controls. Decreased levels of endogenous GR ligand corticosterone and lower expression of 11β‐hydroxysteroid dehydrogenase 1 (11β‐HSD1), a metabolic enzyme that controls corticosterone availability, were found in the livers of Vps15 mutants. Hepatic Vps15 depletion resulted in the activation of nuclear Akt1 signalling, which was paralleled by increased polyubiquitination of GR. Conclusion: In the liver, class 3 PI3K is required for corticosterone metabolism and GR transcriptional activity.